Computer-mediated communication use among adolescents and its implication for psychological need satisfaction - Ang, Chin Siang; Abu Talib, Mansor; Tan, Jo Pei; Yaacob, Siti Nor (Universiti Putra Malaysia Press, 2014)
Online self-disclosure and online communication are two communication behaviours that, on the basis of prior research and theory, would appear to be related both to one another and to psychological need satisfaction. This study explored these relationships among a sample of 190 secondary school students drawn from a district in Malaysia. Respondents completed a questionnaire battery, which included measures of online self-disclosure, online communication and psychological need satisfaction. Quantitative data were then entered and analysed via Statistical Package for Social Sciences (SPSS). The results demonstrated that adolescents disclosed more during same-sex interaction than opposite-sex interaction. The findings also showed a positive relationship between online communication and same-sex disclosure for adolescent girls, but not necessarily for boys. Hierarchical regression analyses confirmed that for male and female adolescents, same-sex disclosure, opposite-sex disclosure and online communication were found to be predictive of adolescents' experiences of psychological need satisfaction in online friendships. No interaction effect was found between online self-disclosure and online communication on psychological need satisfaction. The contribution of this study is two-fold. First, currently, little research exists examining the association between online self-disclosure, online communication and psychological need satisfaction in a single published study. Second, we extend previous research with a more nuanced understanding of psychological need satisfaction embedded in the context of CMC.